Perancangan Sistem Pengumpul Data Dengan Internet Of Thing Pada Software Monitoring Banjir Berbasis Geographic Informatin Sistem - Aziz, Fauzan Zulfa; Suryamen, Haris (Universitas Andalas, 2022)
Flooding is one of the natural disasters that often occur in various regions in Indonesia. Flood events have a negative impact on the community because it can cause material losses and fatalities. Flood disasters generally occur in the rainy season with high rainfall. Technology can be used to reduce the impact caused by the flood disaster. In this study, a system was created that can estimate the probability of flooding by measuring rainfall levels, and changes in water height from ground level by using rain gauge sensors and ultrasonic sensors and sending sensor reading data and flooding positions to the database using the GSM SIM800L Module. Based on this research, the system can estimate the likelihood of flooding and give a warning with a 100% success rate.